2013
DOI: 10.3151/jact.11.144
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Blast Resistance of SIFCON

Abstract: Slurry infiltrated fiber concrete (SIFCON) have received considerable attention in recent years. The SIFCON is distinguished from the conventional steel fiber reinforced cementitious composite (FRCC) by its high volume ratio of fibers, far beyond that of typical steel FRCC. Although this material has already been used for important structures including power plants and military facilities, very little is known about its behavior under blast loading. We therefore have experimentally investigated the behavior of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Additionally, by applying semantic segmentation in this study, it may be possible to propose a new direction in the evaluation of damage based on the image. For example, it is considered possible to obtain more information from images such as those after SIFCON blast obtained from the author's study (Chun et al 2013), and we are currently prompting the study of these.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, by applying semantic segmentation in this study, it may be possible to propose a new direction in the evaluation of damage based on the image. For example, it is considered possible to obtain more information from images such as those after SIFCON blast obtained from the author's study (Chun et al 2013), and we are currently prompting the study of these.…”
Section: Resultsmentioning
confidence: 99%
“…Although the upper limit of the fiber volume fraction is currently about 3% in conventional FRCC, SIFCON can achieve a value of more than 10%. Regarding the blast resistance of SIFCON, Sun et al (1999) and Chun et al (2013) showed that SIFCON slabs or blocks subjected to contact detonation are excellent at reducing damage. Their conclusions were derived from experimental data in which the entire bottom surface of a SIFCON specimen was supported by a steel sheet or soil, but because stress waves may penetrate steel sheets or soil under such conditions, the spall-reducing performance of SIFCON, which directly leads to secondary injury, was not evaluated in those studies.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on a mechanical characteristic of SIFICON were adopted. Increased in the compressive, flexural, and tensile strength was singed for concrete [21][22][23][24]. High volume fiber in the SIFCON significantly improved properties such ductility, toughness, durability, and compressive and flexural strengths [25][26][27][28][29][30].…”
mentioning
confidence: 97%